Elemental distribution and phase composition of Pd-Gd thin films - Xuandong Kou; Noemi Cerboni; Robert Eichler; Malgorzata Makowska; Elisabeth Müller; Matthias Muntwiler; Patrick Steinegger; Emilio A. Maugeri (Materials & Design)
Pd-Gd samples, intended as model of target materials for nuclear physics experiments, were produced via molecular plating followed by coupled reduction. Using high-resolution X-ray diffraction, performed with a highly focused X-ray beam at the Swiss Light Source, at the Paul Scherrer Institute, the formation of single intermetallic GdPd3 compounds dispersed within a Pd-Gd solid solution were identified. A homogeneous distribution of Gd was detected throughout the thickness of the samples. The micro-scale analysis provided detailed insights into the phase composition and elemental distribution, revealing that due to the low Gd concentration used, the bulk structure is likely predominantly a Pd-Gd solid solution with uniformly dispersed intermetallic domains, rather than a complete intermetallic single phase. Additionally, Gd-aggregated regions were observed at the samples surface, where µ-XPS measurements revealed the presence of Gd(III), most probably in the form of Gd2O3. This study suggests that previously reported ’intermetallic targets’ were not pure intermetallic compounds and offers design insights for future target manufacturing with similar materials. Furthermore, this study highlights the advantages of using high-resolution micro-characterization techniques.